Antimicrobial properties of chitosan and galactomannan composite coatings and physical properties of films made thereof - Almeida, L. B. S. (2021)
The aim of this study was to produce antimicrobial coatings and films based on the mixture of chitosan and galactomannan from Adenanthera pavonina L., with the incorporation of sodium acetate. The antimicrobial activity of the coatings was evaluated against L. monocytogenes, S. aureus, P. aeruginosa and S. enteritidis. Then the films produced, based on the coating formulations, were characterized in terms of water vapour permeability (WVP), oxygen (O2) and carbon dioxide (CO2) permeability, moisture content (MC), water solubility (S), tensile strength (TS), elongation at break (EB), elastic modulus (EM), opacity and color. The composite coatings with Chi were effective against Gram-negative and Gram-positive bacteria. Films Chi presented the low water solubility and high values of component b*, which indicates the predominance of yellowish coloration and the highest TS values. Films of Chi-Gal-NaA present lower values of S, MC, WVP and EB and is the film presenting the higher value of EM. While for the films of Gal-NaA there was a reduction of the O2 permeability and an increase of CO2 permeability. Chi in combination with NaA can be used in the development of antimicrobial coatings and films for food applications, therefore contributing to food preservation and shelf-life extension.